2018
DOI: 10.3390/molecules23071817
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Tissue-specific Specialized Metabolism in Tieguanyin Tea Cultivar by Untargeted Metabolomics

Abstract: Tea plants produce extremely diverse and abundant specialized metabolites, the types and levels of which are developmentally and environmentally regulated. However, little is known about how developmental cues affect the synthesis of many of these molecules. In this study, we conducted a comparative profiling of specialized metabolites from six different tissues in a premium oolong tea cultivar, Tieguanyin, which is gaining worldwide popularity due to its uniquely rich flavors and health benefits. UPLC-QTOF MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 67 publications
5
21
0
Order By: Relevance
“…These studies indicated that theanine accumulation was dynamically regulated by seasons (Konishi and Takahashi, 1969; Takeo, 1981; Janet et al, 2015), light (Yang et al, 2012; Deng et al, 2013; Chen et al, 2017; Ji et al, 2018; Sano et al, 2018), nutrient levels (Takeo, 1981; Ruan et al, 2007; Ruan et al, 2010; Ruan et al, 2012; Huang et al, 2018; Kc et al, 2018; Zhu et al, 2019), hormones (Li et al, 2016a), developmental stages (Feldheim et al, 1986; Li et al, 2016b; Liu et al, 2017), and stress (Deng et al, 2012; Wang et al, 2016). Theanine accumulation is also highly tissue-and cultivar-dependent (Fang et al, 2017; Liu et al, 2017; Chen et al, 2018a; Chen et al, 2018b). Theanine accumulation, therefore, is dynamic and highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicated that theanine accumulation was dynamically regulated by seasons (Konishi and Takahashi, 1969; Takeo, 1981; Janet et al, 2015), light (Yang et al, 2012; Deng et al, 2013; Chen et al, 2017; Ji et al, 2018; Sano et al, 2018), nutrient levels (Takeo, 1981; Ruan et al, 2007; Ruan et al, 2010; Ruan et al, 2012; Huang et al, 2018; Kc et al, 2018; Zhu et al, 2019), hormones (Li et al, 2016a), developmental stages (Feldheim et al, 1986; Li et al, 2016b; Liu et al, 2017), and stress (Deng et al, 2012; Wang et al, 2016). Theanine accumulation is also highly tissue-and cultivar-dependent (Fang et al, 2017; Liu et al, 2017; Chen et al, 2018a; Chen et al, 2018b). Theanine accumulation, therefore, is dynamic and highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, widely targeted metabolomic analysis involving qualitative and quantitative detection of a high number of primary and secondary metabolites participating in diverse cellular activities [ 28 ] is required for: understanding the biological abilities of individual sesame tissues, a comprehensive analysis of gene-metabolites relationships, and for elaborating a suitable valorization plan of sesame leaves and flowers. This advanced method was useful in profiling tremendous plant species such as rice, tea, and tomato [ 6 , 28 , 29 ]. With the huge superficies of sesame grown annually worldwide, the valorization of wasted sesame biomass would generate additional profits to small-holder farmers and many industries.…”
Section: Introductionmentioning
confidence: 99%
“…Among natural products recognized worldwide with high therapeutic values, the plant's secondary metabolites, including flavonoids, phenolic acids, terpenoids, alkaloids, tannins, and lignans, are the most sought after [1][2][3][4][5]. Studies have revealed that these metabolites occur in plants in a tissue-specific manner, and their content is influenced by the genetic and environmental factors [6][7][8][9]. In sesame, the diversity of bioactive phytochemicals is still not well understood.…”
mentioning
confidence: 99%
“…Chemical profiling analysis was performed according to previous methods [49,50]. Briefly, freeze-dried tea leaves were individually ground to fine powders using precooled mortar and pestle.…”
Section: Methodsmentioning
confidence: 99%